Prevalence of Tooth Shade and its Correlation with Skin Colour- A cross-sectional study - Asif Iqbal, Fatima Ikram, Mobin Riaz, Momina khalid, Aman Mansoor, Javeria Iftekhar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The significance of aesthetics has become a significant concern in recent years. One of the elements that determine one’s beauty is the colour of one’s teeth. Gender, age, eyes and skin colour as well as other variables have all been found to impact tooth shade in studies. Aim: To find out that how tooth shade relates to the skin colour. Methods: This cross-sectional, analytical research was performed in the Operative Dentistry Department. Over a year, 250 patients between the ages of 18 and 68, of either gender, participated. The complexion of the skin on the face was assessed and split into three skin tone categories (Fair, Medium, and Dark). Results: SPSS version 20.0 was used to analyse the data. There were 162 males and 88 females among the 250 participants. 45.2% of patients was Value 2, which was followed by Value 3 (31.2%), Value 1 (13.2%), and Value 4. (10%). Value 5 had no shadows recorded. The skin tone of the male participants was medium, whereas the skin tone of the female participants was fair. Conclusion: A lower tooth shade value was found in people with fair skin, resulting in teeth that looked darker in colour. A greater tooth shade value was found in those with a darker skin complexion, leading in teeth that seemed lighter in colour. When comparing the tooth colours of men and women, men had a lower shade value while women had a greater shade value. The teeth of the older people were darker in colour because of a significant decrease in lower tooth shade value. Keywords: Skin tone, Shade guide, Tooth colour, gender